Peran Negara Dalam Hubungan Tenaga Kerja di Indonesia - Subijanto -- (Jurnal Pendidikan dan Kebudayaan, 2011)
The aim of this writing article is to identify the function of the Indonesian Government in relation with Indonesian labor force and the relation of labor force organization. Until now, the foundamental problem of the Indonesian job seekers is lack of functional basic skill. Globalization era, has requirement for every job seekers to have competence and to be able to competitive in certain job qualification requirement. Based on the legal formal, the Indonesian labourforce has been protecting by a number of laws, namely: 1) the amandement of the 1945 Constitutionof the Republic of Indonesia (article,27 sub article (2) stated that every citizen shall have the right job and welfare for human being; 2) the act number 39, year 1999 about Human Right an article 38 sub article 1 stated that every citizen, according to potential talent, skill, and smart, shal have the right job. Furthermore, subarticle 2 stated that every people shall have the freedom of choice according to interest and requirement accordingly. Subarticle 3 stated that every people, event women or man to be equal in doing job according to the status of bwckground to get wage in order to be sustainable life; and 3) the act number 13, year 2003 about labour force. In relation with preparation of job seekers the Ministry of National Education (MoNE) has obligation to improve the quality of education and relevance with outcome of education.Meanwhile, the Ministry of Manpower and Transmigration has responsible anda specific task to do the competence of certification through National Board of Proffesional Standard (BNSP) and Institution of Proffesional Standar (LSP).Â ABSTRAKTujuan penulisan ini dimaksudkan untuk mengidentifikasi peran Pemerintah terhadap ketenagakerjaan di Indonesia dan hubungannya dengan organisasi ketenagakerjaan. Permasalahan tenaga kerjaan di Indonesia sampai saat ini masih belum sirna dari permasalah yang mendasar yaitu kurang memiliki keterampilan fungsional bagi calon pencari kerja. Era globalisasi menuntut calon pencari kerja mampu berkompetisi dan memiliki kompetensi yang memadai sesuai dengan persyaratan tutututan kualifikasi pekerjaan. Dari aspek yuridis formal, tenaga kerja di Indonesia telah dilindungi oleh peraturan perundang-undangan, antara lain: (a) UUD Republik Indonesia Tahun 1945 Amandemen, Pasal 27 ayat (2) yaitu â€œTiap-tiap warga negara berhak atas pekerjaan dan penghidupan yang layak bagi kemanusiaanâ€;Â (b) UU Nomor 39/1999 tentang Hak Asasi Manusia,Pasal 38 ayat (1); Ayat (2); Ayat (3); Ayat (4); danÂ (c) UU Nomor 13/2003 tentang Ketenaga-kerjaan. Dalam aspek pendidikan, Kemdiknas berkewajiban untuk meningkatkan mutu dan relevansi hasil pendidikan, sedangkan Kemenakertrans bertanggungjawab dalam pemberian hak melakukan sertifikasi kompetensi melalui Badan Nasional Standar Profesi (BNSP) dan Lembaga Sertifikat Profesi (LSP).